(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2019)
The research focuses on errors detected in learning difficulties (reading), applied in the urban context in the city of Pamplona, at the San Francisco de Asís Archdiocesan Technical Institute, Santa Marta Campus, and in the rural context in the municipality of Pamplonita, Norte de Santander, at the Nuestra Señora del Pilar Educational Institution, Camilo Daza Campus, located in the village of San Rafael. The methodological reference focuses on qualitative, descriptive research. The method used is case studies, and the phenomenon addressed from a qualitative approach is learning difficulties. The technique used is structured interviews. The results show that teachers do not implement strategies that facilitate overcoming difficulties, and sometimes they are not interested in providing timely support to students during the reading process.